The Impact of Company Characteristics on Return Volatility in Sorted Portfolios: A Hybrid Asymmetric Conditional Variance Approach - Seyed Kazem Ebrahimi; Mahnaz Khorasani; Mina Saba (Iranian Journal of Accounting, Auditing & Finance)
The primary objective of this study is to investigate how various stock portfolio strategies affect the volatility of returns among companies listed on the Tehran Stock Exchange (TSE). A systematic elimination method selected 185 companies from 2011 to 2022. The return volatility of these companies, along with the stability of fluctuations, was analyzed across 16 sorted portfolios based on three characteristics: size, book-to-market (B/M) ratio, and financial leverage. Additionally, considering the leveraged structure of companies’ balance sheets, the extent of the leverage effect was examined in relation to the impact of positive and negative news on return fluctuations. The hybrid model ARMA(p, q)-GJR-GARCH(1, 1)-M was utilized to investigate this. The findings indicate that the volatility of returns and the stability of fluctuations within sorted portfolios vary across different groups. Furthermore, the influence of positive news on stock return volatility appears to be more pronounced in two specific portfolios: one consisting of large companies with a high B/M ratio and the other comprised of large companies with a low B/M ratio, compared to the impact of negative news. This disparity may be attributed to the dissemination of positive news within the market, wherein larger companies with low B/M ratios, due to their higher growth potential, and larger companies with high B/M ratios, due to their substantial capital and stable financial performance, have a greater impact on market expectations, thereby enhancing investor confidence.